Pengaruh Media Komik Dan Poster Terhadap Pengetahuan Gizi Seimbang Anak Sekolah: The Effect Of Comic And Poster Media On Balanced Nutrition Knowledge Of School Children - Kaluku, Khartini (Svasta Harena: Jurnal Ilmiah Gizi, 2023)
Background: Due to a lack of awareness about balanced nutrition requirements, school-age children are currently struggling with a variety of nutritional issues, including undernutrition and excess nutrition. The purpose of this study was to compare the impact of comic books and posters on children's knowledge of a balanced diet. Methods: This type of research is a quasi-experimental design with a pre-post test with control. The research location was at the Ambon City Orphanage with 60 school children aged 10-12 years as subjects. The independent variable is the use of comics and posters in balanced nutrition counseling, while the dependent variable is children's knowledge. At the beginning and end of the study, children's knowledge was measured by a questionnaire. Data analysis used paired sample test and independent samples T-test. The results showed that there was a significant increase in knowledge of balanced nutrition in orphanage children before and after being given comic media and posters with a p-value <0.05. Counseling with poster media is more effective in increasing nutrition knowledge than comic media.